PERAN DAN STRATEGI MEDIATOR DALAM PENCEGAHAN PERCERAIAN STUDI KASUS PENGADILAN AGAMA JOMBANG - Chaerudin Loma Faisal; Ahmad Faruq (JURNAL ILMIAH NUSANTARA, 2025)
A mediator is a neutral third party, where one of the functions of a mediator is as a mediator for both parties in a dispute in finding a solution to their conflict so that they can avoid divorce. Mediation, which is one of the mediator's duties, is not only about mediating and listening to the conflict that is the root of the problem, but the mediator in mediation must be able to bring both parties in a dispute into a good discussion so that it ends in the desired agreement without any coercion so that it does not need to go through a long and tiring trial. The focus of this study is on the role of the mediator judge and what strategies are used to prevent divorce. This study discusses the role and strategies used by mediators in preventing divorce at the Jombang Religious Court. The reason for this study was the large number of divorce cases that went to court, so mediation is an important step that must be maximized. The researcher used a qualitative method with an active interview technique with the mediators who were actively on duty. From the results of the interview, it was found that the mediator not only acted as a mediator, but also played a role as an empathetic listener and a provider of solution-oriented advice. The strategies they use include personal and religious approaches, rebuilding communication between husband and wife, and helping them identify the root of the problem more openly. This study shows that mediation can be an effective middle way to maintain the integrity of the household, as long as the process is carried out with patience, expertise, and support from the court environment.